People of the Book dan Gagasan Pluralisme Keagamaan dalam Alquran - Asep Muhamad Iqbal (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
To a certain extent, globalization has provided religions with opportunities to play their roles more extensively and encounter each other more openly than before. In addition to its advantages, this has created a tendency of rigid and exclusive ways of religiosity among different religious believers when they encounter each other or with other cultures. For most believers, this is a way of claiming religious identities, which should be maintained and defended. This article deals with what Islam as a system of belief has contributed to religious pluralism. Using the thematic method of interpretation, it focuses on its analysis on Quranic verses of Ahl al-Kitab, a term that refers to People of the Book. The article argues that from the Quranic perspective, religious pluralism is valid and constitutes one of the main principles of Quranic teachings. Religions of People of the Book differ in terms of syir’ah and minhaj, but they at the same time share a substantial similarity in terms of din, which is seen in their shared doctrine of monotheism (tawhid). To this monotheism, Alquran calls other religions to find a common term. This inclusive religiosity plays as the basis of how Alquran responds to other religions: it acknowledges their validity as systems of belief and emphasizes the shared point as seen in its response to the opposition of People of the Book in the early Islam (Jews and Christians).